Modeling and Simulation of a Photovoltaic Field for 13 kW - Salah Eddine Mankour; Ahmed Wahid Belarbi; Mohammed Tarik Benmessaoud (International Journal of Electrical and Computer Engineering (IJECE), 2017)
In the future solar energy will be very important source of energy. More than 45% of needed energy in the world will be generated by photovoltaic module. Therefore it is necessary to concentrate our efforts in order to reduce the application costs .This work investigates on the modeling of a Stand Alone Power System focusing on Photovoltaic energy systems. We introduce the models of the system components Therefore a maximum power point tracking (MPPT) technique is needed to track the peak power in order to make full utilization of PV array output power under varying conditions. This paper presents two widely-adopted MPPT algorithms, perturbation & observation (P&O) and incremental conductance (IC).A complete characterization and simulation model was implemented in the Matlab-Simulink environment. Design complete system is done to analyze its behavior for a typical year, with the aim to evaluate their energetic effectiveness.